Systemic Treatment for Metastatic Biliary Tract Cancer: State of the Art and a Glimpse to the Future - Alessandro Rizzo; Angela Dalia Ricci; Antonio Cusmai; Silvana Acquafredda; Giuseppe De Palma; Giovanni Brandi; Gennaro Palmiotti (Current Oncology, 2022)
Recent years have seen some breakthroughs in the therapeutic landscape of advanced biliary tract cancer (BTC). Firstly, a better understanding of the molecular background of BTC has led to important improvements in the management of these hepatobiliary malignancies, with the advent of targeted agents representing an unprecedented paradigm shift, as witnessed by the FDA approval of pemigatinib and infigratinib for FGFR2-rearranged and ivosidenib in IDH1-mutant cholangiocarcinoma. In addition, several novel treatments are under assessment, including immune checkpoint inhibitors and combination chemotherapies. In the current review, we provide an overview of systemic treatment for metastatic BTC, summarizing recent clinical data on chemotherapy as well as the main results of targeted therapies and immunotherapy.